Postmodern Tourism Attraction in Tawangmangu SubDistrict, Indonesia: Potential and Development Strategy - Edi Setiawan; Yasin Yusup; Rita Noviani (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
This research aims to describe postmodern tourism attractions, in the form of potential and suggestions for development strategies that can be done in the tourist area of Tawangmangu Sub-District. This study uses a qualitative method with a case study approach. The case study in this study is a postmodern tourism object in Tawangmangu Sub-District, Karanganyar, Indonesia. Qualitative analysis to illustrate the attractions of postmodernism and SWOT analysis to determine usable development strategies. The results show that the potential of postmodernism tourism attractions in Tawangamangu Sub-District is a combination of natural potential in the form of atmosphere, temperature, and beauty of the location on the West Slope of Mount Lawu; and potential attractions made by developers, some of them: Sakura Hills, The Lawu Park, Sekipan Hill, New Balekambang, Kampung Halloween, and Rumah Atsiri Indonesia. Development suggestions can be done by optimizing strengths and potentials by minimizing weaknesses and threats. The situation in the postmodernism era brings diversity, one of which is diversity in the construction of tourism attractions. Postmodern tourism object has a variety of shapes and designs, accommodating patterns from inside and outside Indonesian culture. To face the development of postmodern tourism development, the active role of the community is needed to anticipate the inclusion of culture from outside that is not following Indonesian culture, and not to weaken the culture of the local community itself.